2004
DOI: 10.1073/pnas.0404208101
|View full text |Cite
|
Sign up to set email alerts
|

Folate biofortification in tomatoes by engineering the pteridine branch of folate synthesis

Abstract: Plants are the main source of folate in human diets, but many fruits, tubers, and seeds are poor in this vitamin, and folate deficiency is a worldwide problem. Plants synthesize folate from pteridine, p-aminobenzoate (PABA), and glutamate moieties. Pteridine synthesis capacity is known to drop in ripening tomato fruit; therefore, we countered this decline by fruit-specific overexpression of GTP cyclohydrolase I, the first enzyme of pteridine synthesis. We used a synthetic gene based on mammalian GTP cyclohydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 37 publications
10
135
1
1
Order By: Relevance
“…H 4 BPt does not occur in plants (Kohashi et al, 1980;Díaz de la Garza et al, 2004;Hossain et al, 2004), but it is widely used to assay the activity of AAHs for which it is not the in vivo cofactor (Leiros et al, 2007;Siltberg-Liberles et al, 2008;Pey and Martinez, 2009). Tests with the natural (R) and unnatural (S) forms of H 4 BPt showed that only the R form was active and that the S form had no inhibitory activity (see Supplemental Figure 4 online).…”
Section: Biochemical Characterization Of Pine and Moss Aahsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 4 BPt does not occur in plants (Kohashi et al, 1980;Díaz de la Garza et al, 2004;Hossain et al, 2004), but it is widely used to assay the activity of AAHs for which it is not the in vivo cofactor (Leiros et al, 2007;Siltberg-Liberles et al, 2008;Pey and Martinez, 2009). Tests with the natural (R) and unnatural (S) forms of H 4 BPt showed that only the R form was active and that the S form had no inhibitory activity (see Supplemental Figure 4 online).…”
Section: Biochemical Characterization Of Pine and Moss Aahsmentioning
confidence: 99%
“…The main plant pterins are the folate synthesis intermediates dihydroneopterin, dihydromonapterin, and hydroxymethyldihydropterin (Kohashi et al, 1980;Díaz de la Garza et al, 2004; Hossain et al, 2004;Orsomando et al, 2006). These might be reduced to the tetrahydro level by a dihydropterin reductase like those in bacteria or protists (Gourley et al, 2001;Pribat et al, 2010).…”
Section: Identity Of the Physiological Cofactormentioning
confidence: 99%
“…3C), and increased GCH1 activity only affects the cytosolic (pterin) branch. In previous studies, the overexpression of GCH1 has resulted in massive increases in pterin levels but only a doubling of folate levels, presumably because the plastidial p-aminobenzoate (PABA) branch was depleted (20,21). Similar limitations affected plants with the PABA branch enhanced by overexpression of aminodeoxychorismate (ADC) synthase (ADCS), reflecting depletion of the pterin branch (22).…”
Section: Analysis Of Folate Levels In Transgenic Plants the Expressimentioning
confidence: 95%
“…A significant proportion of plant folates exists in a polyglutamylated form (Storozhenko et al 2007, Orsomando et al 2005, Díaz de la Garza et al 2004). This study has employed LC-MS/MS to reveal that approximately 40% of rice folate forms detected in leaf and 20% of folate in seed exists either as tetra or penta forms of the 5-CH 3 -and 5/ 10-CHO-H 4 Pte ( Table 2).…”
Section: Discussionmentioning
confidence: 99%